2018
DOI: 10.3389/fnhum.2018.00111
|View full text |Cite
|
Sign up to set email alerts
|

A Knowledge-Based Arrangement of Prototypical Neural Representation Prior to Experience Contributes to Selectivity in Upcoming Knowledge Acquisition

Abstract: Knowledge acquisition is a process in which one actively selects a piece of information from the environment and assimilates it with prior knowledge. However, little is known about the neural mechanism underlying selectivity in knowledge acquisition. Here we executed a 2-day human experiment to investigate the involvement of characteristic spontaneous activity resembling a so-called “preplay” in selectivity in sentence comprehension, an instance of knowledge acquisition. On day 1, we presented 10 sentences (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 98 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…Several studies have shown that machine learning can estimate correspondence between several tasks (task labels) and task-induced brain activities (data) (Haynes and Rees 2005a , b ; Haynes and Rees 2005a , b ; Kamitani and Tong 2005 , 2006 ; Norman, et al 2006 ; Ogawa and Imamizu 2013 ). In fact, several studies have also adopted this approach to identify specific information represented in the resting-state brain activity (Deuker 2013 ; Kurashige et al 2018 ; Schapiro et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that machine learning can estimate correspondence between several tasks (task labels) and task-induced brain activities (data) (Haynes and Rees 2005a , b ; Haynes and Rees 2005a , b ; Kamitani and Tong 2005 , 2006 ; Norman, et al 2006 ; Ogawa and Imamizu 2013 ). In fact, several studies have also adopted this approach to identify specific information represented in the resting-state brain activity (Deuker 2013 ; Kurashige et al 2018 ; Schapiro et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon suggests that hippocampal activation during rest may function not only in memory consolidation and retrieval but also in the planning stage. A recent human fMRI study also reported preplaylike activations for the acquisition of new semantic knowledge (Kurashige et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…This phenomenon suggests that hippocampal activation during rest may function not only in memory consolidation and retrieval but also in the planning stage. A recent human fMRI study also reported preplay-like activations for the acquisition of new semantic knowledge (Kurashige et al, 2018). Considering these previous studies, the current finding may also reflect preplay-like activations for learning visuomotor skills, which should be investigated in the future.…”
Section: Discussionmentioning
confidence: 95%
“…Along similar lines, a recent study in humans 1 It has recently been suggested that this finding may only be obtained if the animal is already familiar with the spatial environment or the goal, but the path to the goal is novel. has found that a "Prototypical Neural Representation" measured several minutes prior to the experimental task predicted understanding of sentences (26). Within the domain of episodic memory, studies investigating processes occurring prior to encoding in humans have found that memory may be enhanced by providing what has been termed an "episodic specificity induction" task, in which participants are briefly trained on recalling details of an event prior to encoding (e.g., 27,28).…”
Section: Main Textmentioning
confidence: 99%